2018
DOI: 10.3389/fphys.2018.00637
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Sex-Related Differences in Motor Performance During Sustained Maximal Voluntary Contraction of the First Dorsal Interosseous

Abstract: Age and sex affect the neuromuscular system including performance fatigability. Data on performance fatigability and underlying mechanisms in hand muscles are scarce. Therefore, we determined the effects of age and sex on force decline, and the mechanisms contributing to force decline, during a sustained isometric maximal voluntary contraction (MVC) with the index finger abductor (first dorsal interosseous, FDI). Subjects (n = 51, age range: 19–77 years, 25 females) performed brief and a 2-min sustained MVC wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 67 publications
0
9
1
Order By: Relevance
“…Exclusion criteria included psychiatric disorder, neurologic disease (including previous TBI), and drug or alcohol abuse. Data from the control subjects were also used in an accompanying study (Sars et al, 2018). Experiments were designed in accordance with the declaration of Helsinki (World Medical Association, 2013) and approval of the experimental procedures was provided by the medical ethical board of the University Medical Center Groningen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusion criteria included psychiatric disorder, neurologic disease (including previous TBI), and drug or alcohol abuse. Data from the control subjects were also used in an accompanying study (Sars et al, 2018). Experiments were designed in accordance with the declaration of Helsinki (World Medical Association, 2013) and approval of the experimental procedures was provided by the medical ethical board of the University Medical Center Groningen.…”
Section: Methodsmentioning
confidence: 99%
“…Next, group (mTBI) was added to the basic model as a fixed effect. Since sex and age can affect the time-related changes in force and EMG (Sars et al, 2018), we subsequently included these variables and their interactions to the model in a stepwise fashion. Model residuals were examined graphically for normality and heteroscedasticity (using quantile-quantile plots and heteroscedasticity plots) for all multilevel models.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, during the sustained muscle action at RPE = 2, the men decreased force nearly twofold more than the women (61.0% vs. 34.7%). These findings were typical of fatigue-related differences between men and women [17,28,33,35,36], but this is the first study to report a sex-related difference in performance fatigability following a muscle action anchored to a perception of exertion as opposed to a relative force value. Typically, sex-related differences are more pronounced following low-intensity than high-intensity sustained isometric muscle actions due to differences in the amount of muscle mass activated, which, in theory, leads to differences in muscle blood flow and neuromuscular responses between men and women [5,17,18,28,36].…”
Section: Discussionmentioning
confidence: 54%
“…Both sex-related differences (time to exhaustion and muscle activation) disappeared when repeated under an ischemic condition [5], which suggested that the differences were blood flow dependent [33]. Furthermore, Sars et al [35] recently hypothesized that sex-related differences in performance fatigability may be more influenced by peripheral factors such as fiber type distribution and intramuscular pressure than central factors such as neural drive and corticospinal excitability. Hunter [18] has previously described "…the magnitude of the sex-differences is specific to the task performed…" (p. 114).…”
Section: Discussionmentioning
confidence: 99%
“…Participants sat in a chair with both forearms on the armrests and the elbows flexed at ~90°. In this position, participants held a force transducer in each hand with the index finger extended and parallel to horizontal bar (see Figure 2) (Sars et al, 2018; Wolkorte et al, 2015). The proximal interphalangeal joint of the index finger was taped to a C‐shaped plastic piece connected to a bar with strain gauges attached to the force transducer for measuring the voluntary index finger abduction force.…”
Section: Methodsmentioning
confidence: 99%